EKSPOSUR KONTEN LGBT: DAMPAK IDENTITAS SEKSUAL ANAK PERSPEKTIF AL-QUR’AN DAN LITERASI DIGITAL - Peni Alyanita; Bayu Agung Maulana; Pathul Mubin; Muhammad Fikri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital media has changed children's socialization patterns, including the formation of sexual identity. The high use of social media exposes children to various content, including LGBT issues, which has the potential to influence their values and perceptions. This research aims to analyze the impact of digital content exposure on children's sexual identity from the perspective of Quran-based family education and the role of digital literacy as a protective mechanism. This research uses a qualitative approach with a library research design and interdisciplinary conceptual analysis. Data were obtained from the Quran, tafsir, and scientific sources, and then analyzed thru content and thematic analysis. The research results show that social media functions as a dominant agent of digital socialization thru algorithmic mechanisms, filter bubbles, and echo chambers. Repeated exposure has the potential to cause cognitive dissonance, value relativization, and shifts in children's moral orientation. In the perspective of the Qur'an, human identity is part of fitrah (QS. Ar-Rum: 30), reinforced by the prohibition of deviation (QS. Al-A’raf: 80–84) and the command to maintain purity (QS. An-Nur: 30–31). The integration of digital literacy and Quran-based family education becomes an effective and constructive protective strategy in preserving children's identity in the digital era.